Adherence to a Mediterranean Dietary Pattern and Functional Parameters: A Cross-Sectional Study in an Older Population - Mendes, J (2020)
Objectives: In older adults, diet and physical activity are among the most important behaviours that influence health. The Mediterranean Dietary Pattern has been related to longevity and can benefit physical function in older adults. The present study aims to quantify the association of adherence to a Mediterranean Dietary Pattern with physical functioning through by handgrip strength, as well as, with sedentary behaviour based on sitting time, in a sample of older adults. Methods: A cross-sectional study was conducted in 1,491 older adults ≥ 65 years old. The adherence or non-adherence to a Mediterranean Dietary Pattern was assessed using the previously validated and translated 14 item questionnaire, the PREDIMED (Prevención com Dieta Mediterránea). Handgrip strength was measured with a Jamar Dynamometer. Sitting time per day was used as an indicator of sedentary behaviour. Multinomial logistic regressions were performed to quantify the association of adherence to a Mediterranean Dietary Pattern with handgrip strength and sitting time. Results: Compared to participants who adhered to a Mediterranean Dietary Pattern, those who did not adhere to this diet have a significantly higher adjusted odds ratio for low handgrip strength [adjusted odds ratio: 1.50; 95% confidence interval: 1.09-2.05], as well as for longer sitting time [adjusted odds ratio: 1.43; 95% confidence interval: 1.04-1.96]. Conclusion: In older adults, the non-adherence to a Mediterranean Dietary Pattern was associated with both lower values of handgrip strength and longer sitting time.